The Application of Multiple Attribute Decision in LED Commerce Platform - Huahuan LEI; Lilan LIU; Tao YU (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The paper applied multiple attribute decision making into LED collaborative commerce platform to help customers make purchase decision. The normal customers are unfirmiliar with LED lighting product, because it is latest product in lighting industry and the attributes of LED are complicated and professional. The method analyzed the essential attributes and network attributes of LED lighting products to sequence the limited alternative. And based on the shortage of TOPSIS method, the paper combined grey correlation with TOPSIS method in order to make decision more exactly. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2382